Role of Laparoscopy in Management of Ectopic Pregnancy (Journal of Enam Medical College, 2015)
Ectopic pregnancy means implantation of fertilized ovum outside the endometrial lining of the uterus. It remains the leading cause of early pregnancy-related death. Delay in diagnosis and treatment puts the life of women at risk. Laparoscopic surgery is increasingly becoming the preferred approach for ectopic pregnancy management. Laparoscopic treatment in ectopic pregnancy raises question of safety and feasibility when compared to laparotomy. In this review article our objective is to summarize the role of laparoscopy in management of ectopic pregnancy in comparison to laparotomy. For this, a literature search was done by using Google and PubMed. The selected articles were analyzed on laparoscopic treatment outcomes such as surgery success rate, operating time, intraoperative and postoperative complications, hospital stay, future fertility, postoperative recurrent ectopic pregnancy, cost-effectiveness in comparison to laparotomy. After analyzing all selected articles, it can be concluded that the laparoscopic management of ectopic pregnancy is safe, effective, and economical in comparision to laparotomy. So, for the patients benefit, laparoscopy should be considered as the gold standard method in management of ectopic pregnancy and is worthy to be popularized in clinical practice.J Enam Med Col 2015; 5(3): 170-174